PENGEMBANGAN ALAT PERAGA ALAM KAPAS (ALARM, LAMPU, DAN KIPAS ANGIN PANEL SURYA) UNTUK MENUMBUHKAN LITERASI SAINS - Estuhono, Estuhono; Anggrayni, M.; Aprido, Tri (Information Technology Education Department, 2025)
This study was motivated by the limited creative thinking skills and understanding of students regarding the topic of alternative energy. Therefore, the researchers aimed to develop a teaching aid called ALAM KAPAS (Alarm, Lamp, and Fan Powered by Solar Panels). This research employed a development research (R&D) approach using the 4-D development model, consisting of the stages of define, design, develop, and disseminate. The validation results for the ALAM KAPAS teaching aid, assessed by three experts, showed an average score of 96.55%, categorized as highly valid, based on components such as the teaching aid itself, practical guidelines, and student worksheets. Practicality assessment by classroom teachers resulted in an average score of 95%, categorized as highly practical. The effectiveness of the teaching aid was supported by cognitive assessments with an average score of 94.86% and psychomotor assessments of students with an average score of 85.14%. This study concludes that the ALAM KAPAS teaching aid for science subjects, particularly on the topic of alternative energy sources and simple creations, meets the criteria of being highly valid, highly practical, and highly effective.